Automated LPG Monitoring and Rebooking System using IoT- A Review - S., Rajkumar; S., Venkatanathan; P., Prasanth (Journal of ISMAC, 2024)
LPG (Liquified Petroleum Gas) has become an essential requirement in daily life, as many people rely on it for cooking, fueling vehicles, and more LPG offers a portable, clean, and efficient alternative to traditional fossil fuels, making it especially valuable for rural and urban areas in India. By replacing wood, coal, and other traditional fuels, LPG enhances health, air quality, and overall comfort. To simplify the LPG rebooking process for domestic and commercial use, various applications have been developed. This study presents a brief overview of existing research on LPG monitoring systems and proposes a method for automatic rebooking by monitoring LPG consumption in real-time and triggering an automatic refill request when the gas level reaches a predefined threshold. The system also provides users with notifications and updates about the status of the LPG, further enhancing convenience and reliability.